Entwicklung einer Methode für die Prognose des Anziehdrehmoments von Kunststoffmutte - Wippermann, Jan; Meschut, Gerson (JOINING PLASTICS)

Numerical modeling of clamp load relaxation of plastic nuts under varying moisture and fiber content - Wippermann, Jan; Meschut, Gerson
This study presents a numerical approach using a 3D finite element model to quantify the remaining clamp load of a plastic nut joint after a specific time. The viscoelastic relaxation of a thermoplastic nut, which is predominantly screwed on a welding stud, is described by a material card using Prony Series. Prony Series are derived from experimental Dynamical Mechanical Analysis with different moisture and fiber contents of the thermoplastic. Since plastic nuts usually do not have preformed threads, the increased temperatures and resulting stresses from the thread-forming process are considered in the simulation. Firstly, the FE model is verified by substrate stress relaxation tests. Subsequently, experimental clamp load measurements with miniature compression load cells verify the clamp load prediction. Finally, the developed model is used to analyze the clamp load distribution within the threads

Effect of Water Absorption on the Clamp Load of Plastic Nuts - Wippermann, Jan; Meschut, Gerson (Proceedings of the Munich Symposium on Lightweight Design 2023)

Analyse des Ein- und Überdrehmoments von Kunststoffmuttern in Abhängigkeit von der Luftfeuchtigkeit - Wippermann, Jan; Meschut, Gerson (JOINING PLASTICS)

Entwicklung einer Methode zur Prognose der Verschraubungsparameter von Kunststoffmuttern - Wippermann, Jan; Meschut, Gerson (14 Gemeinsames Kolloquium Zur Mechanischen Fügetechnik)

Flexible Automation through Robot-Assisted Mechanical Joining in Small Batches - Neumann, Stefan; Wippermann, Jan; Meschut, Gerson; Stepputat, Marten; Beuss, Florian; Flügge, Wilko

Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koschukow, Wikentji; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Influence of plasma coating pretreatment on the adhesion of thermoplastics to metals - Wippermann, Jan; Koshukow, Wikentij; Liebsch, Alexander; Kolbe, Björn; Meschut, Gerson; Gude, Maik (Tagungsband Münchener Leichtbauseminar 2022)

Thermal influence of resistance spot welding on nearby overmoulded plastic metal joints - Wippermann, Jan; Meschut, Gerson; Koschukow, Wikentji; Liebsch, Alexander; Gude, Maik; Kolbe, Björn; Minch, Steven (IIW2022, Annual Assembly, Commission III)

Flexible Teilautomatisierung des robotergestützten mechanischen Fügens - Wippermann, Jan; Meschut, Gerson; Stepputat, Marten; Flügge, Wilko (12. Gemeinsames Kolloquium zur Mechanischen Fügetechnik)